Effect of an agglomeration-suppressed metal island buffer layer on nanostructure of FePt-oxide granular films for heat assisted magnetic recording media - Kim Kong Tham; Ryosuke Kushibiki; Daiki Miyazaki; Shin Saito (Journal of Science: Advanced Materials and Devices)
Investigation of nanostructure and magnetic properties of granular films deposited with a Carbon-Pt buffer layer (BL) as an agglomeration-suppressed metal island BL is reported. Compared with the granular film deposited on an agglomerated BL, Carbon BL, grains separation are promoted. BL with thickness thicker than 0.6 nm and Pt content of 40–70 vol% in the BL is effective to suppress the grain agglomeration. Similar to Carbon BL, (001) in-plane component in the granular film fabricated with Carbon-Pt BL is also reduced significantly. The suppression of material diffusion from BL to the granular films will enhance magnetic anisotropy energy of the granular films.